Understanding the Data Gaze and Students’ Improvisation of Passages on Chinese MOOCs - Zhang, Jingyi (Proceedings of the International Conference on Networked Learning, 2026)
A powerful, though not universal, imaginary that posits the ‘rational’ nature of data appears to have taken hold, particularly in the field of digital education. Ranging from invisible learning analytics to self-tracking applications that visualise students’ learning activities, data—or, in many respects, performance data—are regarded as indispensable for driving data-led insight and foresight in education practices. Yet, these metrics often create a space for surveillance in which the data gaze produces meaning and reinforces entrenched educational assumptions. This paper examines the complexity of this gaze within Massive Open Online Courses (MOOCs), platforms that were once heralded as revolutionary for massifying higher education and facilitating connectivist learning. Specifically, focusing on XuetangX, one of the largest MOOC platforms in China, this study investigates the persistent score indicator on the course learning page, aiming to understand how this indicator ‘gazes’ upon individual students and the way the gaze is returned. This research, rooted in phenomenology, conducted interviews with students from elite Chinese universities to acquire an understanding of their lived engagement with XuetangX. Drawing upon Beer’s theory of the data gaze, the study positions the score indicator as the ‘gazer,’ with students occupying the role of the ‘gazees.’ Viewed through the gazer’s lens, the findings reveal the neoliberal principles underlying the performative gaze of this score indicator, which privileges a fixed model of education and renders individuals responsible for their own learning progress. However, the gaze is not unidirectional or passively received. An interpretation of the students’ responses to the score indicator using Ingold’s more-than-human perspectives unravels different ‘lines’ through which these university students strategically resist the data gaze. Rather than reproducing the preconceived educational assumptions, the gazees are found to be improvising specific passages by ‘swiping’ their way into the gaze. The paper subsequently argues that the data gaze on XuetangX is a dynamic, non-static ‘line of becoming’ where the ongoing educational reality is co-responded, unfolding in the space between the gazer’s expectations and the gazees’ agencing. This theorisation provides critical insights into how data both performs and is performed in the high-stakes context of the Chinese higher education system.